Surface Wave Mitigation Algorithm for Bandwidth Enhancement in Microstrip Circular Patch Antennas - T. Mary Neebha, A. Diana Andrusia, P.Malin Bruntha, J.Grace Jency (International Journal of Advanced Science and Technology, 2020)
Diffraction from the edges of a microstrip patch antenna is a major concern in implantable antennas. Microstrip antennas suffers from one of the major problems of low-quality factor (narrow bandwidth), primarily due to the excitation of surface waves over the patch. To overcome this, the dominant mode created in the patch should be eliminated completely. The proposed method in this work is to reduce the coupling between adjacent elements using Modified-Surface Wave Analysis and Reduction Theorem (M-SWART). The method suggests that by properly choosing the effective dielectric constant below the patch, dominant mode can be eliminated. Surface wave elimination effectively results in bandwidth enhancement and in turn increases the radiation efficiency of the prototype. In this work, conventional circular antenna is considered as an example to verify Modified - SWART. The circular patch antenna designed using M-SWART algorithm is designed using electromagnetic solver. Keywords: Surface waves, bandwidth, patch antenna, mode